Information on the absence of specific substances in food in the regulations of food law - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2018)
This article presents general requirements laid down in food law regarding information on the absence of specific substances in food. The author noted, among other things, that the fact that not uniform solutions for certain types of designations (e.g. sugar-free, gluten-free) are adopted demonstrates the lack of a coherent EU legislator’s policy in this area. As a result, the consumer’s interests are not adequately protected. Given the variety of regulations, this leads at times to “statutory misrepresentation.” Hence the call for unification of regulations informing about the absence of specific substances in food.